2011
DOI: 10.1089/ten.tec.2011.0212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypertonic (NaCl) Two-Dimensional and Three-Dimensional Culture Conditions on the Properties of Cartilage Tissue Engineered from an Expanded Mature Bovine Chondrocyte Source

Abstract: Clinically relevant mature cartilage cells (chondrocytes) present challenges for use in cartilage tissue engineering applications, given their low capacity for cell division and tissue production. Since the in situ environment of chondrocytes is hypertonic relative to standard culture medium conditions, in this study we tested the hypothesis that using culture medium of a hypertonic, more physiologic osmolarity during both two-dimensional (2D) expansion of mature bovine chondrocytes (MBCs) and their subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
3
16
2
Order By: Relevance
“…The present study revealed that hyperosmolarity (450mOsm) applied to self-assembled chondrocytes reduced only collagen content. This result is in contrast to the increased collagen content seen in agarose-embedded chondrocytes (Sampat et al, 2013), but in agreement with the decreases seen with expanded chondrocytes (Oswald et al, 2011). The discrepancy in hyperosmolarity’s effects on ECM production suggests that further optimization of hyperosmotic loading levels in neocartilage engineering is needed.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The present study revealed that hyperosmolarity (450mOsm) applied to self-assembled chondrocytes reduced only collagen content. This result is in contrast to the increased collagen content seen in agarose-embedded chondrocytes (Sampat et al, 2013), but in agreement with the decreases seen with expanded chondrocytes (Oswald et al, 2011). The discrepancy in hyperosmolarity’s effects on ECM production suggests that further optimization of hyperosmotic loading levels in neocartilage engineering is needed.…”
Section: Discussionsupporting
confidence: 83%
“…Applied to agarose-encapsulated articular chondrocytes, hyperosmolarity (400mOsm) elicited significant increases in tensile stiffness and GAG and DNA content (Sampat et al, 2013). In contrast, when applied to 2D-expanded chondrocytes in hydrogels, hyperosmolarity (400mOsm) decreased Young’s modulus, and GAG, collagen, and DNA content (Oswald et al, 2011). The present study revealed that hyperosmolarity (450mOsm) applied to self-assembled chondrocytes reduced only collagen content.…”
Section: Discussionmentioning
confidence: 98%
“…While modulating glucose concentration affects the medium osmolarity, and osmotic environment changes have been shown to have an impact on chondrocyte metabolism, 57,58 the osmolarity change elicited in this study by reducing glucose was low compared to osmolarities previously studied, and therefore the resulting changes in tissue properties are likely attributed to the concentration of glucose. Due to their lower medium concentrations, altering the concentrations of insulin, transferrin, selenous acid, or ascorbate does not elicit substantial changes in the medium osmolarity.…”
Section: Its Ascorbate and Glucose On Engineered Cartilage Growthmentioning
confidence: 57%
“…It is well known that chondrocytes would undergo a dedifferentiation process which is considered as progressive change of their rounded morphology 22 and gradually loss of their chondrogenic capacity with further monolayer culture. 23 During the 27,28 adopting various cell densities 29,30 or ameliorating cell culture conditions like hypoxic 31 or hypertonic 32 environments.…”
Section: Introductionmentioning
confidence: 99%